Hyperandrogenism in women with polycystic ovary syndrome persists after menopause - Markopoulos, M.C.; Rizos, D.; Valsamakis, G.; Deligeoroglou, E.; Grigoriou, O.; Chrousos, G P; Creatsas, G.; Mastorakos, G. (Journal of Clinical Endocrinology and Metabolism, 2011)
Context: Ovarian and adrenal hyperandrogenism characterize premenopausal women with polycystic ovary syndrome (PCOS). Androgens decline with age in healthy and PCOS women. Objective: The objective of the study was to investigate hyperandrogenism in PCOS after menopause. Design: This was a case-control, cross-sectional study. Setting: The study was conducted at a university hospital endocrinology unit. Patients: Twenty postmenopausal women with PCOS and 20 age- and body mass index-matched controls participated in the study. Interventions: Serum cortisol, 17-hydroxyprogesterone (17-OHP), Δ4- androstenedione (Δ4A), dehydroepiandrosterone sulfate (DHEAS), total testosterone (T), and free androgen index (FAI) levels were measured at baseline, after ACTH stimulation, and after 3-d dexamethasone suppression. The ACTH and cortisol levels were measured during the CRH test. Main Outcome Measures: Androgen profile at baseline, after ACTH stimulation, and 3-d dexamethasone suppression tests were the main outcome measures. Results: Postmenopausal PCOS women had higher 17-OHP, Δ4A, DHEAS, total T, FAI (P < 0.05) and lower SHBG (P<0.05) baseline levels than control women. ACTH and cortisol responses during the CRH test were similar in the two groups. After ACTH stimulation, Δ4A, DHEAS, and total T levels were equally increased in both groups. After dexamethasone suppression, LH levels did not change in either group; 17-OHP-, Δ4A-, and FAI-suppressed levels remained higher in PCOS than in control women (P < 0.05), whereas total T and DHEAS levels were suppressed to similar values in both groups. Conclusions: In postmenopausal PCOS women, ACTH and cortisol responses to CRH are normal. Androgen levels at baseline are higher in PCOS than control women and remain increased after ACTH stimulation. The dexamethasone suppression results in postmenopausal PCOS women suggest that DHEAS and total T are partially of adrenal origin. Although the ovarian contribution was not fully assessed, increased Δ4A production suggests that the ovary also contributes to hyperandrogenism in postmenopausal PCOS women. In conclusion, postmenopausal PCOS women are exposed to higher adrenal and ovarian androgen levels than non-PCOS women. Copyright © 2011 by The Endocrine Society.